PERANAN DANA PERIMBANGAN DALAM PEMBIAYAAN PENYELENGGARAAN PEMERINTAHAN DAERAH DI KABUPATEN BANYUMAS - Haedah Faradz (Notary Master Programe, Faculty of Law Universitas Jenderal Soedirman, 2018)
Tax as a source of income for state finance is a manifestation of the community's direct contribution to development goals. The Regional Government of Banyumas Regency on September 10, 2004 proposed the Acquisition of Non-Taxable Tax Objects to the Minister of Finance and based on the Decree of the Head of Regional Office of the Directorate General of Taxation of West Java dated Dec-ember 23, 2004, Kep 14 /WPJ 10/BD05/2004 determine the amount of the acquisition value of non-taxable objects in Banyumas Regency. The problem examined in this paper is The Role of Balancing Funds originating from the Fees for Acquiring Land and Building Rights in financing the administration of regional government in Banyumas Regency; and Factors that influence the receipt of balance funds from the Land and Building Rights Acquisition Fees in Banyumas Regency. The research method used was normative juridical, namely statue approach and conceptual approach then analyzed qualitatively. The cost of acquiring land and building rights (BPHTB) in financing the administration of regional government in Banyumas Regency was still relatively small, and its implementation was also influenced by several factors. Keywords: tax, Customs for Land and Building Rights, locally-generated revenue.